THE IMPACT OF REAPPLYING FACE TO FACE LEARNING IN THE NEW NORMAL ERA ON THE ENGLISH ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS AT SMPN 1 MAKALE SELATAN - Tantri Palosong (Publikasi dan UKI Press UKI Toraja., 2023)
The objective of this research is to find out the impact of reapplying face to face learning in the new normal era on the English achievement of the eighth-grade students at SMPN 1 Makale Selatan. In analyzing the data of this research, the writer used qualitative method. The subject of this research were the English teacher and students at SMPN 1 Makale Selatan. The data of this research was collected by doing interview. The obtained data were analyzed in three major phases namely reduction, data display, and conclusion. The result of the research found out some the impact of reapplying face to face learning in the new normal era on the student’s English achievement, the first there is students learning motivation, the second it is easier for students to understand the material provided by the teacher in class, and the third students English achievement have increased face to face learning is reinstated. Based on these findings, the researcher concluded that the current reapplying of face-to-face learning hase every positive impact on students’ English achievement